Synthesis and Biological Evaluation of 1-(6-chlorobenzo [d]thiazol-2-yl)-2-(disubstituted methylene) hydrazine derivatives - Sharma, Neetesh Kumar; Bhadauria, Raghvendra Singh (Journal of Drug Delivery and Therapeutics, 2019)
Synthesis of a series of various 1-(6-chlorobenzo[d]thiazol-2-yl)-2-(disubstitutedmethylene)hydrazine derivatives (7a-7e)have been done. Synthesis of a series of intermediates (3 and 5) have been also done, 6-Chloro-2-amine-1,3-benzothiazole (3), 2-hydrazino-6-chloro-1, 3-benzothiazole (5) and final product (7a-7e), 1-(6-chlorobenzo[d]thiazol-2-yl)-2-(diphenylmethylene) hydrazine (7a), 1-(6-chlorobenzo [d]thiazol-2-yl)-2-(propan-2-ylidene) hydrazine (7b), (E)-2-(butan-2-ylidene)-1-(6-chlorobenzo[d]thiazol-2-yl)hydrazine (7c), (Z)-1-(6-chlorobenzo[d]thiazol-2-yl)-2-(cyclohexylmethylene) hydrazine (7d), 2-(6-chlorobenzo[d]thiazol-2-yl)-1-(7,7- dimethylbicyclo [2,2,1] heptan-2-ylidene)hydrazine (7e). Spectral analysis of all intermediates and final products has been done by IR and NMR. After spectral analysis, antibacterial activity has been screened against S. aurius and E. coli bacterias.